PENGARUH PENGETAHUAN DAN IKLAN TERHADAP MINAT MENABUNG DI BANK SYARIAH (STUDI MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM IAIN PADANGSIDIMPUAN ANGKATAN 2014) - FADLI, FADLI (Imara: JURNAL RISET EKONOMI ISLAM, 2017)
Syariah Banking is an Islamic banking which has main function to deploy and distribute funds to society. Islamic banking is a relevance ?inancial institution to Islamic principles such as Al qur?an and Hadist. The condition of Islamic banking at state institute for Islamic studies, Padang Sidempuan was many students preferred to learn about banking, Islamic law, Islamic syariah bank, and syariah bank, from the available bank advertisement like magazines, newspapers, radio, television, and others.